2021
DOI: 10.3390/ijms22041703
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Wide Analysis of Stationary Phase Small ncRNAs in E. coli

Abstract: Almost two-thirds of the microbiome’s biomass has been predicted to be in a non-proliferating, and thus dormant, growth state. It is assumed that dormancy goes hand in hand with global downregulation of gene expression. However, it remains largely unknown how bacteria manage to establish this resting phenotype at the molecular level. Recently small non-protein-coding RNAs (sRNAs or ncRNAs) have been suggested to be involved in establishing the non-proliferating state in bacteria. Here, we have deep sequenced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 74 publications
2
31
0
Order By: Relevance
“…Co-culture of human 5' tRNA halves with F. nucleatum inhibits bacterial growth, likely through interference with bacterial protein biosynthesis (He et al, 2018). Several studies have also demonstrated that environmental stress increases cytosolic tRNA halves in microbes (Thompson et al, 2008;Garcia-Silva et al, 2010;Fricker et al, 2019;Raad et al, 2021); however, the function of 5' and 3' tRNA halves induced by stress remains elusive.…”
Section: Microbial Trna Fragments and Their Cell-autonomous Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-culture of human 5' tRNA halves with F. nucleatum inhibits bacterial growth, likely through interference with bacterial protein biosynthesis (He et al, 2018). Several studies have also demonstrated that environmental stress increases cytosolic tRNA halves in microbes (Thompson et al, 2008;Garcia-Silva et al, 2010;Fricker et al, 2019;Raad et al, 2021); however, the function of 5' and 3' tRNA halves induced by stress remains elusive.…”
Section: Microbial Trna Fragments and Their Cell-autonomous Effectsmentioning
confidence: 99%
“…ContinuedRaad et al, 2021 of note. Is the production and packaging of tRNA fragments into microbial EVs regulated?…”
mentioning
confidence: 99%
“…The CsrA-interacting sRNA CsrB (Liu et al, 1997) was also recovered in the same fractions (Figure 5A). However, full-length tRNA Gly and its 5'-tRNA fragment, a stationary-phase enriched sRNA that we previously recovered (Raad et al, 2021), were both largely depleted from these fractions (Figure 5A) thus highlighting the specificity of the experimental system. Taken together, these pulldown data confirmed that fimR2 and CsrA interact in vivo.…”
Section: Fimr2 Interacts With Csramentioning
confidence: 69%
“…This suggested that the sRNA is important for stationary phase-specific phenomena. To gain insight into possible fimR2 functions, we ectopically expressed this sRNA in an inducible manner during exponential phase (Raad et al, 2021).…”
Section: Fimr2 Promotes Stationary Phase-dependent Biofilm Formationmentioning
confidence: 99%
“…The initial fortuitous finding of ribosome-bound ncRNAs in polysome-derived RNA-sequencing data [ 33 ], which were probably prematurely referred to as ‘contaminants’, has fostered more dedicated research on the ribosomal ncRNA interactome. In the recent past, our laboratory conducted several targeted RNome screens for ribosome-associated ncRNA in various model organisms spanning all three domains of life ( Figure 2 ) [ 15 , 20 , 21 , 34 , 35 ]. To detect novel ncRNAs putatively regulating the ribosome’s activity, various stress conditions were applied to the different model systems.…”
Section: Methodologies For the Identification Of Rancrnasmentioning
confidence: 99%